OHP-019 Assessment of four manual infusion devices of [18f]-fluorodeoxyglucose in a nuclear medicine department. (25th February 2017) - Dekyndt, B; Nachon, P; Legrand, JF; Semah, F
Abstract : Background: In nuclear medicine, [18F]-fluorodeoxyglucose (18-FDG) is usually administered in unit doses partitioned from multi-dose vials in radiopharmacy. Administration can be performed manually or automatically. In a nuclear medicine department where the dispensing system used is the Unidose by TRASIS, administrations have to be performed manually. The infusion sets selected should reduce radiation exposure to the staff involved, improve administration accuracy and mitigate contamination. Purpose: To assess four infusion devices. There is no guideline for the 18-FDG infusion device. Material and methods: The evaluation focused on five criteria: The feasibility of infusion device by in vitro assessment of a dye path into the tubing. The ergonomics of use by staff evaluated with a satisfaction scale. The skin exposure of staff hands measured by thermoluminiscent dosimeters placed on three staff fingers during infusion. The 18-FDG adsorption in the tubing by measuring residual radioactivity after infusion and rinsing. The devices costs. The four devices tested were: (1) a conventional infusion device with a 3 way stopcock (n=10), (2) a device with a 3 way stopcock and 2 non-return valves (n=9), (3) an infusion device marketed by DORAN with a 3 way stopcock and two non-return valves (n=8) and (4) a device marketed by TRASIS without a 3 way stopcock but with 2 non-return valves (n=6). Results: The feasibility study revealed that device (4) showed a slight dye path in the opposite direction of the infusion. The ergonomics study revealed that the luer-lock movable extremities for devices (1) and (4) and the length of devices (3) and (4) were appreciated. The staff hands skin's exposure indicated relative improvement in radioprotection with devices (3) and (4) (respectively, 4.61 and 521.10 -5 mgy/MBq and 9.24 and 643.10 -5 mgy/MBq for devices (1) and (2), respectively) if we focus on the most exposed finger. The 18-FDG adsorption showed no significant difference between devices (< 0.01% of initial radioactivity, p < 0.05). The price gradually increased between devices (1) and (4) (from €0.4 to €4.97 TTC/device). Conclusion: The results suggest staff choices as device (3) or (4). Nevertheless, staff training is necessary for optimal use of these devices. No conflict of interest